Faktor-faktor yang mempengaruhi tingkah laku antisosial dalam kalangan pelajar di empat sekolah daerah Johor Bahru - Taat, Suhaila (2010)
Social problems and antisocial which involved adolescents are increasing and are becoming serious. These problems if not attended will bring negative impact towards the development of student’s self-concept which can affect the development of the nation in future. It is assumed that many aspects contribute to this problem. This research focuses on four aspects which are self oncept, parenting style, peer influence and environmental factor. A total of 250 form four student from School A, School B, School C and School D students participated in the research. Questionnaires were given to the subjects in order to gather information. Frequency, mean, standard deviation, t test, correlation and multiple regression were used to analyze the data. This study found that antisocial behavior is most often done by student is truancy with higher mean 3.588. Research results also show that there is a significant relationship between concept and antisocial behavior at the significance level of 0.05. However the ‘r ’ value of is only 0.318. Overall parenting style also has a significant relationship with antisocial behavior at the significance level of 0.05 and ‘r ’ value of 0.111. Peers and environmental factor also has significant relationship with antisocial behavior at significant level 0.05 and ‘r ’ value 0.116 and 0.170 respectively. For multiple correlations showed self concept independently contributed significantly to the antisocial behavior of 2.8 percent of the variance in the criterion changes (antisocial behavior). The value of this correlation will increase by 1.8 percent to 4.6 percent when the combination of predictors involving self concept and peer factors to changes in the criterion variance (antisocial behavior). Suggestions are proposed to parents, educators, teachers and the society in order for them to plan and provide conducive environment and activities that can enhance good behavior among adolescents in the light that they will not involve in social ills and antisocial behavior.